Comparison of factors associated with leukemia and lymphoma mortality in Brazil - Marcela de Sá Gouveia; Jessica Keyla Matos Batista; Taciana Silveira Passos; Beatriz Santana Prado; Carlos Eduardo Siqueira; Marcos Antonio Almeida-Santos (Cadernos de Saúde Pública, 2020)
Abstract: In the last decades, few epidemiological studies have discussed the mortality rates due to leukemia and lymphoma in Brazil. This study analyzes the evolution over time of the number of deaths due to leukemia and lymphoma in Brazil, between 2010 and 2016, considering the population’s characteristics and spatial distribution. This is a retrospective epidemiological study based on data obtained in the Brazilian Health Informatics Department (DATASUS), associated with the quantitative population. We created choropleth maps and predictive models of mortality rates, using the incidence rate ratio (IRR) to measure the size of the effect. Leukemia had a 1.76 higher mortality rate than lymphoma. Leukemia mortality trends increased by 1.2% per year between 2010 and 2016. Regions with the lowest social inequality had higher mortality rates for both diseases. There was a difference between peaks with higher chances of death due to leukemia (> 60 years) and lymphoma (> 70 years). Older age, male, white, and South and Southeast regions were associated with higher mortality by leukemia or lymphoma.